2013
DOI: 10.1155/2013/217864
|View full text |Cite
|
Sign up to set email alerts
|

Role of NHE1 in Nociception

Abstract: Intracellular pH is a fundamental parameter to cell function that requires tight homeostasis. In the absence of any regulation, excessive acidification of the cytosol would have the tendency to produce cellular damage. Mammalian Na+/H+ exchangers (NHEs) are electroneutral Na+-dependent proteins that exchange extracellular Na+ for intracellular H+. To date, there are 9 identified NHE isoforms where NHE1 is the most ubiquitous member, known as the housekeeping exchanger. NHE1 seems to have a protective role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
2
11
0
Order By: Relevance
“…Our results correspond well with the former data published showing that blockade of peripheral, as well as spinal, NHE1 by administration of selective and non-selective inhibitors, such as zoniporide, amiloride, and 5-(N,N-dimethyl)-amiloride increased pain behavior in capsaicin, serotonin, and formalin tests [73][74][75][76]. In line with these experiments, electrophysiological studies showed that the blockade of NHE1 can modulate electrical activity of primary nociceptive terminals [47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results correspond well with the former data published showing that blockade of peripheral, as well as spinal, NHE1 by administration of selective and non-selective inhibitors, such as zoniporide, amiloride, and 5-(N,N-dimethyl)-amiloride increased pain behavior in capsaicin, serotonin, and formalin tests [73][74][75][76]. In line with these experiments, electrophysiological studies showed that the blockade of NHE1 can modulate electrical activity of primary nociceptive terminals [47].…”
Section: Discussionsupporting
confidence: 92%
“…The reduction of NHE1 functional expression seems to be beneficial to conserve paracellular BBB integrity, however, the data showing facial sensitivity induced by a single, systemic dose of zoniporide raises question about the overall positive effect of NHE1 blockade in migraine/secondary headache patients. The role of NHE1 in nociception has been recently discovered, suggesting a protective role of NHE1 in acute and chronic inflammatory pain [47]. Our results correspond well with the former data published showing that blockade of peripheral, as well as spinal, NHE1 by administration of selective and non-selective inhibitors, such as zoniporide, amiloride, and 5-(N,N-dimethyl)-amiloride increased pain behavior in capsaicin, serotonin, and formalin tests [73][74][75][76].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NHE1 is the most extensively studied of the four isoforms. It has been implicated in pain 35 , several diseases, e.g. myocardial hypertrophy 36 and cancer.…”
Section: Sodium-hydrogen Exchanger1 (Nhe1)mentioning
confidence: 99%
“…However, other scenarios could explain the amiloride effect on gene expression. Zhou et al pointed to the role of NHE1, the most ubiquitous member of the mammalian Na + /H + exchanger family [ 21 , 38 ], as a signaling protein involved in gene expression regulation [ 39 ]. In the brain of a spontaneous NHE1 null mutant mouse strain, several genes were significantly up- or downregulated.…”
Section: Discussionmentioning
confidence: 99%